Effect of environmental salinity and dopamine injections on key digestive enzymes in hepatopancreas of the euryhaline crab Cyrtograpsus angulatus (Decapoda: Brachyura: Varunidae - Michiels, Maria Soledad (2013)
We studied the occurrence and characteristics of lipase activity and the response of lipase and proteolytic activity to salinity and dopamine injections in hepatopancreas of the euryhaline crab (Cyrtograpsus angulatus). Lipase activity was maximal at pH 8.5; it exhibited Michaelis-Menten kinetics (apparent Km=0.019 mM), was higher at 37°C and appeared to be cold tolerant, being also high at 4°C. In 10 psu (hyper-regulation conditions), lipase and proteolytic activity were about 3 and 5 times higher, respectively, than in 35 psu (osmoconformation). In 40 psu (hypo-regulation), lipase activity was about three times higher than in 35 psu, while proteolytic activity was similar. Lipase activity was inhibited in vivo by 10–4 M dopamine in 35 psu but not in 10 or 40 psu. Proteolytic activity was not affected by 10–4 M dopamine. The differential responses of lipase and proteolytic activity to salinity and dopamine suggest the occurrence of distinct digestive adjustments and mechanisms of regulation upon osmoregulatory conditions. This study contributes to a better understanding of the complexity of the biochemical adaptations to salinity in euryhaline crabs. The fact that higher digestive enzyme activities could be associated with a differential digestive capacity potentially leading to enhanced availability of energy substrates is discussed.